ANALISIS PERAN AKTOR DALAM IMPLEMENTASI PROGRAM KOTAKU (KOTA TANPA KUMUH) DI KELURAHAN BANDARHARJO SEMARANG UTARA, KOTA SEMARANG - Joanne Endamia Ameita Purba; Aufarul Marom (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
Slum settlements are a serious problem for developing countries. The Indonesian government has carried out many programs to overcome this problem, one of which is the KOTAKU (Cities Without Slums) Program, regulated in SE Minister of PUPR Number 40 of 2016 about general guide the KOTAKU Program. The KOTAKU Program builds collaboration between government and non-government. The purpose of this research is to know the roles of the actors involved in the implementation of the KOTAKU Program and the they faced when implementing program in Kelurahan Bandarharjo. This is a descriptive qualitative research, using interviews, observations, and documentations, analyzing the resulting findings to make conclusions. The research found that the actors involved in KOTAKU Program implementation in Kelurahan Bandarharjo play their roles in accordance to their position, including Bapedda as the KOTAKU Program Lead at the city level, Korkot KOTAKU as the consultant and facilitator, Kelurahan Bandarharjo as companion of implementation, BKM as construction implementer, as well as the commmunity as beneficiaries. The implementation has a problem, such as: misunderstandings with the community, Covid-19 outbreak, and executive transfers at the city level. The findings are analyzed and shows that the actors performed their roles well, resulting in the program reaching its sustainability stage. This research recommends all actors involved to increase their contribution in dealing with slum settlements problem, so that actors collaboration can realize public welfare of livable home.